Jan Nepomucen Józef Braun (1926–2015), filolog klasyczny, orientalista, kartwelista, sumerolog - Witczak, Krzysztof Tomasz (Collectanea Philologica, 2021)
Jan Braun, born on 15th May 1926 in Łódź, studied classical philology and classical archaeology at the University of Lodz (years 1947–1951). His MA thesis (1951) was devoted to the ethnogenesis of the Etruscans. He also worked as junior assistant at the Department of Classical Archaeology, University of Lodz (from May 1949 do September 1950) and later as junior lecturer at the Department of Classical Philology of the same university (from October 1950 to September 1951). In October 1951, Braun left for Georgia in order to complete his doctoral studies. From there he returned to Poland as PhD, specializing in Georgian and other oriental languages, especially the ancient languages of the Near East. In the years 1955–2002, he worked at the University of Warsaw, initially as assistant professor. In 1970, he became associate professor. In 1991, he received the higher doctoral degree (habilitation), and in 1995 he obtained the position of full professor. He studied the genetic relations of ancient and modern languages, including a suggested Basque-Kartvelian connection. During his habilitation colloquium, he gave an interesting lecture entitled Basic problems of historical-comparative research over the ancient languages of the Mediterranean area (Warsaw, May 28th, 1991), which is presented in Appendix No. 1 (with some comments and bibliographical references). The paper presents Braun’s main fields of research and his achievements made in Łódź (Poland), Tbilisi (Georgia) and Warsaw. According to Braun’s view, suggested as early as 1951, Etruscan represents an external member of the Anatolian languages (deriving from Luwian), so that it belongs to the Indo-European language family. In his opinion, Basque is a western member of the South Caucasian (or Kartvelian) family.